PENGARUH JENIS BAHAN BAKAR BIOBRIKET TERHADAP UNJUK KERJA PADA MINIATUR PEMBANGKIT LISTRIK TENAGA UAP - Narti, Narti; Zelviani, Sri; Wahidah, Nurul; Abadi, Firdaus Alam; Ihsan, Ihsan (Universitas Islam Negeri Alauddin Makassar, 2019)
Research has been conducted to determine the effect of biobriquette fuel types on electric power generated in miniature steam power plants. This study uses four fuels, namely raw materials for coconut shell and wood, and biobriquette from coconut shell and wood. There are two parameters tested in this study, namely the burning time and evaporation of 2000 ml of distilled water and the electric power generated. Based on research that has been done it can be concluded that the type of fuel influences the amount of power produced. From the type of fuel obtained that the greater the calorific value of a fuel, the electric power produced will be greater as well. small heating value of around 3000 cal / g, the electric power produced is getting smaller, that is equal to 0.0021 watts.